Growth Response of Tomato Plants (Lycopersicum esculentum Mill.) to Liming and Fertilizer Types on Acid Soils - Yakop S. Laginda; Hayatiningsih Gubali; Sutrisno Hadi Purnomo (International Journal of Technology and Education Research, 2026)
Acid soils with low pH are a major constraint for tomato cultivation in Indonesia, including in Kwandang District, North Gorontalo Regency, which has a soil pH of 5.23. This study aimed to determine the growth response of tomato plants (Lycopersicum esculentum Mill.) to liming and fertilizer types on acid soils. The research was conducted in Molingkapoto Village, Kwandang District, North Gorontalo Regency, for four months (November 2025–February 2026). A Factorial Randomized Block Design was employed with two factors: agricultural lime dosage (K0 = no lime; K1 = 1,000 g/plot; K2 = 1,300 g/plot) and fertilizer type and dosage (P0 = no fertilizer; P1 = organic fertilizer 7,000 g/plot; P2 = NPK fertilizer 8 g/plant), replicated three times for 27 experimental units. Parameters observed included plant height, leaf number, leaf color score, and leaf area index at 14, 30, and 44 days after planting (DAP). Results showed that liming at 1,300 g/plot (K2) and NPK fertilizer at 8 g/plant (P2), both independently and in combination (K2P2), produced the best growth across all parameters at 44 DAP: plant height, leaf number, leaf color score, and leaf area index. Liming improved soil pH and increased macro and micronutrient availability, while NPK fertilizer provided essential nutrients rapidly available to the plant.